Composition of zinc-lead halide quasi-two-dimensional green light perovskite and preparation method and application thereof
By introducing zinc and the additive BPCA into lead-based halide perovskite light-emitting diodes, a zinc-lead halide quasi-two-dimensional green light perovskite composition is prepared, which solves the challenges of environmental protection and optoelectronic performance of existing PeLEDs. Efficient and stable photoelectric conversion efficiency and extended device life are achieved.
Patent Information
- Application Number
- CN202411243276.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-05
AI Technical Summary
Existing lead-based halide perovskite light-emitting diodes (PeLEDs) have challenges in improving photoelectric performance and environmental protection, especially because the toxicity of lead poses an environmental and health threat, limiting its commercial application.
By introducing zinc (Zn) as a partial replacement element for lead (Pb) and using the additive [bis(4-methoxyphenyl)phosphoryloxy]tert-butyl carbamate (BPCA), zinc-lead halide quasi-diodes were prepared The composition of dimensional green light perovskite optimizes the structure and performance of the material.
Significantly improves the external quantum efficiency (EQE) of PeLEDs from 7.1% to 21.5%, extends the T50 life of the device by about 4.3 times, improves the spectral stability and repeatability of the material, and ensures the stability of the production process and products Consistency of quality.
Smart Images

Figure HDA0005029896620000011 
Figure HDA0005029896620000012 
Figure HDA0005029896620000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of microelectronic devices, and in particular relates to a composition of zinc-lead halide quasi-two-dimensional green light perovskite and a preparation method and application thereof. Background Art
[0002] Lead-based halide perovskite light-emitting diodes (PeLEDs), as a highly promising technological innovation, are gradually showing immeasurable application potential in display technology, lighting industry and communications. Since its electroluminescent properties were first revealed, PeLEDs technology has made rapid progress and successfully achieved efficient light emission in the green, red and even near-infrared spectral ranges. This achievement has undoubtedly injected new vitality into the optoelectronic field. Especially in the field of green PeLEDs, researchers continue to explore and innovate, and have proposed a series of cutting-edge strategies such as multi-ligand passivation technology, fine interface engineering and material structure optimization, aiming to significantly improve the radiative recombination efficiency of the device. At present, the external quantum efficiency (EQE) of green PeLEDs has exceeded 30%. This research progress not only demonstrates a major leap in the practical application of perovskite materials, but also indicates that a new chapter in its commercial application is about to begin. However, as a key component of these high-performance materials, the environmental exposure problem of lead cannot be ignored. Lead toxicity poses a severe challenge to the nervous system, children's cognition and growth, kidney function, immune system and even potential carcinogenic risks. This series of environmental problems and toxicity concerns have seriously restricted its market promotion and commercialization as a green and environmentally friendly emerging technology. Therefore, increasing investment in the research and development of environmentally friendly perovskite materials and accelerating its industrialization process have immeasurable value and significance for promoting the sustainable development of the global optoelectronic industry and achieving harmonious coexistence of economy, society and environment.
[0003] At present, the core challenge facing perovskite PeLEDs is to reduce their negative impact on the environment, which is mainly due to the APbX3 compound that most high-performance devices rely on, and its potential toxicity cannot be ignored. According to research, the high symmetry of the APbX3 structure and the Pb 6s 2 6p 0The unique electronic configuration is the cornerstone of its excellent optoelectronic properties. Specifically, the lack of significant bonding-antibonding between the conduction band and the valence band in APbX3 leads to the formation of shallow transition levels by most intrinsic defects, while only a few high-formation-energy defects can trigger deeper transition levels, thus giving the material excellent defect-tolerance properties. In addition, the band edge mainly contributed by the p orbital shows a larger effective mass than the more delocalized s orbital band edge. However, the strong spin-orbit coupling effect in APbX3 cleverly keeps the conduction band edge of the Pb 6p orbital at a smaller effective mass, which helps to achieve efficient and balanced carrier transport and is crucial to improving the performance of optoelectronic materials. Based on these characteristics, two common strategies are used to achieve efficient and environmentally friendly green light APbX3 structures: one is to partially replace Pb to create low-lead perovskites, which not only retains the optoelectronic advantages of Pb but also reduces toxicity; the other is to completely replace Pb and pursue lead-free perovskites, but this puts more stringent conditions on the electronic structure of the replacement element. Since the performance of devices that completely replace Pb is poor, researchers mostly adopt the strategy of partially replacing Pb, introducing metal ions with low toxicity such as tin (Sn), germanium (Ge), and antimony (Sb) to partially replace the B-site Pb ions. However, although this direction shows positive prospects, the external quantum efficiency (EQE) of low-lead green light PeLEDs is generally low, which has become a bottleneck restricting its widespread application. Therefore, improving the optoelectronic properties of low-lead perovskite materials and optimizing device structure and design to overcome this technical obstacle are key issues that need to be urgently addressed in current research. According to relevant research reports, in the innovative exploration of green light PeLEDs, Ge was successfully introduced as a partial replacement for Pb, which significantly reduced the toxicity risk of the material. The prepared Ge-Pb perovskite film has a photoluminescence quantum yield (PLQY) of up to 71%, which is a 34% increase compared to the unsubstituted perovskite film. In addition, the EQE of Ge-Pb-based PeLEDs reached 13.1%, which marked an important progress in the field of perovskite material modification at that time. Although PeLEDs that partially replace Pb have made significant progress in efficiency, stability, and spectral characteristics, there are still a series of challenges and difficulties to overcome in order to further improve the efficiency and stability of perovskite LEDs. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a composition of zinc-lead halide quasi-two-dimensional green light perovskite, and the PeLED device prepared by the composition exhibits excellent spectral stability.
[0005] The present invention also provides a method for preparing a composition of zinc-lead halide quasi-two-dimensional green light perovskite.
[0006] The present invention also provides a perovskite film, wherein the perovskite film is prepared from the composition of the zinc-lead halide quasi-two-dimensional green light perovskite.
[0007] The present invention also provides a perovskite light-emitting diode, comprising an anode conductive glass layer, a hole transport layer, an interface modification layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer which are sequentially stacked, wherein the perovskite light-emitting layer is the perovskite film.
[0008] According to a first aspect of the present invention, a zinc-lead halide quasi-two-dimensional green light perovskite composition is proposed, and the preparation raw materials of the zinc-lead halide quasi-two-dimensional green light perovskite composition include: tert-butyl [bis(4-methoxyphenyl)phosphinoyl]carbamate and zinc bromide.
[0009] According to the embodiment of the first aspect of the present invention, there are at least the following beneficial effects:
[0010] The present invention introduces the environmentally friendly element zinc (Zn), which successfully replaces part of the lead (Pb) component, thereby significantly reducing environmental pollution in the production process. Furthermore, by innovatively integrating the additive [bis(4-methoxyphenyl)phosphinoyl]carbamate tert-butyl ester (BPCA, CAS: 619333-95-8), it not only effectively enhances the comprehensive performance of the device, but also achieves a qualitative leap in multiple key indicators. Compared with the industry benchmark study (Nat. Commun. 2021, 12, 4295), the significant advantage of the present invention is that Zn, which has more abundant reserves and lower costs, is used as an alternative material. Compared with the traditionally used germanium (Ge), this change not only reduces production costs, but also broadens the diversity of material sources. More importantly, the replacement ratio of zinc to lead has been greatly increased from the original 10% to 15%, showing higher environmental benefits and substitution potential. In terms of performance, the present invention has achieved a significant improvement in external quantum efficiency (EQE) from 7.1% to 21.5%. This leap forward means a huge leap in the photoelectric conversion efficiency of the device, providing a more efficient option for applications in related fields. 50 The life span (the time required for the brightness to drop to 50% of the initial brightness) was also extended from a short 0.86 hours to an astonishing 3.72 hours, an increase of about 4.3 times, greatly improving the durability and reliability of the product. In addition, the repeatability of the invention has also been significantly enhanced, ensuring the stability of the production process and the consistency of product quality, laying a solid foundation for large-scale commercial applications.
[0011] In some embodiments of the present invention, the raw materials for preparing the zinc-lead halide quasi-two-dimensional green light perovskite composition further include: cesium bromide, lead bromide, zinc bromide and phenylbutylammonium bromide.
[0012] In some embodiments of the present invention, the molar ratio of the cesium bromide, the lead bromide, the zinc bromide, the phenylbutylammonium bromide and the [bis(4-methoxyphenyl)phosphinoyl]carbamic acid tert-butyl ester is: 1-1.2: 1-x: x: 0.4-0.8: 0.1-0.5; x is 0-30%.
[0013] According to the second aspect of the present invention, a method for preparing the zinc-lead halide quasi-two-dimensional green light perovskite composition is proposed, comprising the following steps: mixing cesium bromide, lead bromide, zinc bromide, phenylbutylammonium bromide and [bis(4-methoxyphenyl)phosphinoyl]carbamic acid tert-butyl ester in a solution state and heating them to react to obtain the composition.
[0014] In some embodiments of the present invention, the heating temperature is 30-60° C., and the heating time is not less than 6 hours.
[0015] In some embodiments of the present invention, in the solution state, Pb 2+ With Zn 2+ The sum of their concentrations is 0.04-0.06 mol / L.
[0016] According to a second aspect of the present invention, a perovskite film is provided, wherein the perovskite film is prepared from the composition of the zinc-lead halide quasi-two-dimensional green light perovskite.
[0017] According to a third aspect of the present invention, a perovskite light-emitting diode is proposed, comprising an anode conductive glass layer, a hole transport layer, an interface modification layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer stacked in sequence, wherein the perovskite light-emitting layer is the perovskite film.
[0018] In some embodiments of the present invention, the method for preparing the perovskite light-emitting diode comprises the following steps:
[0019] S1: After patterning the conductive glass using a laser etching process, ultrasonic cleaning of the conductive glass is performed using acetone, ethanol and deionized water in sequence;
[0020] S2: drying the cleaned conductive glass in an oven to obtain a conductive glass layer, and then immediately transferring the conductive glass to an environment filled with an inert atmosphere (which may be N2);
[0021] S3: depositing a hole transport layer solution on a conductive glass substrate by spin coating, and then performing annealing to obtain a hole transport layer;
[0022] S4: depositing the interface modification layer on the hole transport layer by vacuum evaporation to obtain an interface modification layer film;
[0023] S5: depositing the prepared perovskite precursor solution on the electron transport layer by spin coating, and then performing annealing treatment to obtain a perovskite light-emitting layer;
[0024] S6: depositing an electron transport layer on the light-emitting layer film by vacuum evaporation to obtain an electron transport layer film;
[0025] S7: depositing an electron injection layer on the electron transport layer thin film by vacuum evaporation to obtain an electron injection layer thin film;
[0026] S8: depositing the metal electrode layer on the electrode modification layer film by vacuum evaporation to obtain a metal electrode.
[0027] In some embodiments of the present invention, the conductive glass substrate comprises a glass substrate with indium tin oxide (ITO) plated on its surface.
[0028] In some embodiments of the present invention, in step S1, the ultrasonic cleaning time is not less than 10 minutes.
[0029] In some embodiments of the present invention, in step S2, the drying time is 5-30 minutes, and the drying temperature is 100-150°C.
[0030] In some embodiments of the present invention, in step S3, the material of the hole transport layer includes poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine).
[0031] In some embodiments of the present invention, in a solution state, the concentration of the poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) is 4 to 8 mg / ml.
[0032] In some embodiments of the present invention, in the poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) solution, the solvent is chlorobenzene.
[0033] In some embodiments of the present invention, in step S3, the spin coating parameters are: rotation speed 3000-5000 rpm, and spin coating time 30-120 s.
[0034] In some embodiments of the present invention, in step S3, the annealing temperature is 100-200°C and the annealing time is 10-30 minutes.
[0035] In some embodiments of the present invention, in step S4, the parameters of the vacuum evaporation are: the pressure is 5×10 -5 ~5×10 -4 Pa, coating thickness is 1~5nm, rate
[0036] In some embodiments of the present invention, in step S5, the rotation speed of the spin coating is 3000-5000 rpm, and the spin coating time is 30-200 s.
[0037] In some embodiments of the present invention, in step S5, the annealing temperature is 60-100° C., and the annealing time is 30-300 s.
[0038] In some embodiments of the present invention, the material of the electron transport layer includes at least one of 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene, 4,7-diphenyl-1,10-phenanthroline, 4,7-diphenyl-1,10-o-phenanthroline and 4-biphenyl-bis(2-methyl-8-hydroxyquinoline)aluminum.
[0039] In some embodiments of the present invention, the material of the interface modification layer includes at least one of lithium fluoride and oxoacid-type lithium salt.
[0040] In some embodiments of the present invention, in step S6, the parameters of the vacuum evaporation are: pressure of 5×10 -5 ~5×10 -4 Pa, coating thickness is 20~50nm, rate
[0041] In some embodiments of the present invention, the material of the electron injection layer includes lithium fluoride.
[0042] In some embodiments of the present invention, in step S7, the parameters of the vacuum evaporation are: the pressure is 5×10 -4 ~8×10 -4 Pa, coating thickness is 1-2nm, rate
[0043] In some embodiments of the present invention, in step S8, the parameters of the vacuum evaporation are: the pressure is 5×10 -5 ~5×10 -4 Pa, coating thickness is 100~200nm, rate
[0044] In some embodiments of the present invention, the method for preparing the perovskite light-emitting diode further comprises packaging the prepared perovskite light-emitting diode.
[0045] In some embodiments of the present invention, the encapsulation step includes bonding the obtained device to a glass sheet using ultraviolet curing glue, and then irradiating it with a 365nm ultraviolet lamp for 30-40s for curing. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0047] Figure 1 The structure diagram of the perovskite light-emitting diode device prepared in the embodiment;
[0048] Figure 2 PL spectra of light-emitting layer films with different substitution ratios in the examples and comparative examples;
[0049] Figure 3 The transient fluorescence lifetime spectra of the light-emitting layer thin films of Example 1 and Comparative Example 1;
[0050] Figure 4 PLQY statistics of the light-emitting layer thin film of Example 1 and Comparative Example 1;
[0051] Figure 5 The graphs are current density-voltage-brightness graphs of PeLED devices of the embodiment and the comparative example;
[0052] Figure 6 The current density and EQE diagram of the PeLED devices of the embodiment and the comparative example;
[0053] Figure 7 EL spectra of PeLED devices of the embodiment and comparative example;
[0054] Figure 8 The PeLED devices of Example 1 and Comparative Example 1 were run at T 50 Lifespan graph;
[0055] Fig. 9 It is a two-dimensional pseudo-color contour map of the spectral stability of the PeLED devices of the embodiment and the comparative example at different voltages;
[0056] Fig.10 The PeLED current density-external quantum efficiency (EQE) diagram of Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0057] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0058] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0059] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0060] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0061] Example 1
[0062] This embodiment provides a method for preparing a composition of zinc-lead halide quasi-two-dimensional green light perovskite and a perovskite light-emitting diode, specifically:
[0063] The preparation method of the composition of zinc-lead halide quasi-two-dimensional green light perovskite is:
[0064] CsBr, PbBr, ZnBr, PBABr and BPCA were dissolved in DMSO in a ratio of 1.15:0.85:0.15:0.5:0.2 and mixed to ensure that Pb 2+ With Zn 2+ The sum of the concentrations of the two is 0.05 mol / L. The mixed solution is then placed on a 40° C. hot plate and stirred for more than 6 hours overnight to obtain a composition of zinc-lead halide quasi-two-dimensional green light perovskite (perovskite precursor solution).
[0065] The preparation method of perovskite light-emitting diode is as follows:
[0066] S1: patterning the bottom electrode on the ITO conductive glass substrate by laser etching, and ultrasonically cleaning the etched ITO conductive glass with acetone, ethanol and deionized water for no less than 15 minutes respectively;
[0067] S2: Dry the cleaned conductive glass substrate in an oven at 150°C for not less than 10 minutes to remove moisture from the surface of the substrate, and then immediately transfer the substrate into a glove box filled with inert gas (N2);
[0068] S3: 4 mg / mL TFB solution was spin-coated on an ITO conductive glass substrate at 3000 rpm for 30 s, and then placed on a 135°C heating table for annealing for 20 min. After cooling, a hole transport layer film was obtained.
[0069] S4: Place the ITO substrate with TFB spin-coated on a pressure of 5×10 -4 ~8×10 -4 Vacuum evaporation was performed under the conditions of Pa, using a square mask, the evaporation material was LiF, the coating thickness was 2.5nm, and the rate Obtaining an interface modification layer film;
[0070] S5: Spin coating the perovskite precursor solution on the interface modification layer film, the spin coating speed is 5000 rpm, the spin coating time is 80 s, and annealing is performed immediately after the spin coating is completed, the annealing temperature is 90° C., the annealing time is 60 s, and after cooling, a zinc-lead halide quasi-two-dimensional green light perovskite film is obtained;
[0071] S6: At a pressure of 5×10 -4 Pa conditions, using a square mask, the electron transport layer material is TPBi, the coating thickness is 40nm, and the rate
[0072] S7: At a pressure of 5×10 -4 Pa conditions, using a square mask, the electron injection layer is made of LiF, the coating thickness is 1nm, and the rate is about
[0073] S8: At a pressure of 5×10 -4 Pa conditions, using a strip mask, the cathode material is Al, the coating thickness is 150nm, and the rate
[0074] Finally, the perovskite light-emitting diode was packaged. After the glass sheet was bonded with UV-curing adhesive, it was irradiated with a 365nm ultraviolet lamp for about 30 seconds for curing. The packaging was completed to obtain the perovskite light-emitting diode device preparation.
[0075] Example 2
[0076] The difference between this embodiment and embodiment 1 is that the Pb substitution ratio in the preparation of the perovskite light-emitting layer is 10%. Specifically, CsBr, PbBr, ZnBr, PBABr and BPCA are dissolved in DMSO in a ratio of 1.15:0.9:0.1:0.5:0.2 and mixed, and the rest remain unchanged.
[0077] Example 3
[0078] The difference between this embodiment and embodiment 1 is that the Pb substitution ratio in the preparation of the perovskite light-emitting layer is 20%. Specifically, CsBr, PbBr, ZnBr, PBABr and BPCA are dissolved in DMSO in a ratio of 1.15:0.8:0.2:0.5:0.2 and mixed, and the rest remain unchanged.
[0079] Example 4
[0080] The difference between this embodiment and embodiment 1 is that the Pb substitution ratio in the preparation of the perovskite light-emitting layer is 30%. Specifically, CsBr, PbBr, ZnBr, PBABr and BPCA are dissolved in DMSO in a ratio of 1.15:0.7:0.3:0.5:0.2 and mixed, and the rest remain unchanged.
[0081] Comparative Example 1
[0082] The difference between this embodiment and embodiment 1 is that the Pb substitution ratio in the preparation of the perovskite light-emitting layer is 0. Specifically, CsBr, PbBr, ZnBr, PBABr and BPCA are dissolved in DMSO in a ratio of 1.15:1:0:0.5:0.2 and mixed, and the rest remain unchanged.
[0083] Comparative Example 2
[0084] The difference between this embodiment and embodiment 1 is that potassium p-aminobenzoate (CAS: 138-84-1) is used to replace tert-butyl bis(4-methoxyphenyl)phosphinoyl]carbamate in the preparation of the perovskite light-emitting layer, and the rest remains unchanged.
[0085] Test Case
[0086] Figure 1 This is a structural diagram of a zinc-lead halide quasi-two-dimensional green light perovskite light-emitting diode device, which, from bottom to top, includes anode conductive glass, hole transport layer, interface modification layer, perovskite light-emitting layer, electron transport layer, electron injection layer and cathode.
[0087] Figure 2The photoluminescence (PL) spectra of the light-emitting layer films of Example 1 (replacement of 15%), Comparative Example 1 (replacement of 0%), Example 2 (replacement of 10%), Example 3 (replacement of 20%) and Example 4 (replacement of 30%) are shown. According to the test results, the photoluminescence (PL) spectra of the films prepared by gradually replacing PbBr2 with ZnBr2 at different ratios show a stable trend and no significant changes occur. Specifically, when the substitution ratio of ZnBr2 gradually increases from 0% to 30%, the PL peak wavelength of the film only undergoes a slight blue shift, which is specifically manifested as follows: the PL peak of the unsubstituted (0% ZnBr2) film is located at 505nm, and remains at 505nm after 10% substitution, showing good stability; when further substituted to 15%, the PL peak slightly blue shifts to 504nm; when the substitution ratio reaches 20%, the blue shift phenomenon is more obvious, and the PL peak drops to 503nm; however, even if the substitution ratio increases to 30%, the PL peak slightly rises back to 504nm, but there is still no significant change. In-depth analysis of this series of PL test results shows that the partial substitution of ZnBr2 for PbBr2 does not significantly affect the fluorescence properties of the film, especially in the visible light band, where the fluorescence emission of the film maintains a high degree of stability and consistency.
[0088] Figure 3 The transient fluorescence lifetime spectra of the light-emitting layer films of Example 1 (15% replacement) and Comparative Example 1 (0% replacement). According to the test results, the film prepared by replacing 15% of PbBr2 with ZnBr2 exhibited a significantly prolonged fluorescence decay lifetime. This finding directly proves that the exciton lifetime inside the film after substitution has been effectively prolonged. Specifically, the extension of the exciton lifetime means that in the film, the excitons formed by electrons and holes can exist more stably, reducing the energy lost due to non-radiative recombination paths. This improvement in stability directly promotes the efficiency of the radiative recombination process, allowing more excitons to release energy in the form of luminescence rather than dissipating in the form of heat or other non-light radiation. Furthermore, the extension of the exciton lifetime is also conducive to the effective transmission of energy in the film. During the longer exciton lifetime, the excitons have more time to migrate inside the film and find more suitable recombination sites, thereby improving the efficiency and directionality of energy transfer.
[0089] Figure 4The following is a statistical chart of the photoluminescence quantum yield (PLQY) of the light-emitting layer film of Example 1 (15% replacement) and Comparative Example 1 (0% replacement). According to the test results, the film prepared by replacing 15% of PbBr2 with ZnBr2 exhibited a significantly improved PLQY, specifically, the PLQY of the film was as high as 92.1%, which is extremely excellent among similar materials. In contrast, the PLQY of the film without ZnBr2 substitution (0% substitution, that is, the PbBr2 content remained 100%) was only 60.5%. This sharp contrast strongly illustrates that by precisely controlling the partial substitution of PbBr2 with ZnBr2 (15% in this case), not only the luminous efficiency of the film is significantly improved, but also its ability to effectively convert absorbed energy into light radiation is greatly enhanced. This significant improvement in PLQY, on the one hand, indicates that the introduction of ZnBr2 may optimize the crystal structure of the film, reduce non-radiative recombination centers, and thus promote the radiative recombination process of excitons; on the other hand, it may also be related to ZnBr2 improving the band structure of the film and promoting the effective recombination of electrons and holes. In summary, the film using ZnBr2 to replace 15% of PbBr2 not only reaches a new height in luminous efficiency, but also shows excellent performance in energy conversion efficiency, providing a strong experimental basis and theoretical foundation for the development of high-performance light-emitting devices, improving energy utilization efficiency, and expanding the application field of optoelectronic materials.
[0090] Figure 5 The following is a graph of the current density-voltage-brightness of PeLEDs for Example 1 (15% replacement), Comparative Example 1 (0% replacement), Example 2 (10% replacement), Example 3 (20% replacement) and Example 4 (30% replacement). According to the test results, under the condition of different proportions of ZnBr2 replacing PbBr2, the prepared PeLED showed significant brightness changes. In particular, when the proportion of ZnBr2 replacing PbBr2 reached 15%, the prepared PeLED achieved the highest brightness, with a specific value of 7172 cd / m 2 This result is much better than that without replacement (replacement 0%, brightness is 5926cd / m 2 ) and other replacement ratios (e.g., when replacing 10%, the brightness is 6078cd / m 2 When the replacement rate is 20%, the brightness drops to 5479cd / m 2 When the replacement rate is 30%, the brightness is further reduced to 3497cd / m 2) of PeLED. Higher brightness means that PeLED using ZnBr2 instead of 15% PbBr2 can convert more electrical energy into light energy with extremely high efficiency during electroluminescence. This improvement in conversion efficiency not only reflects the optimization of the electron-hole recombination mechanism inside PeLED, but also shows that the adjustment of material structure and energy band arrangement helps to reduce non-radiative recombination losses, allowing more energy to be released in the form of photons.
[0091] Figure 6 The current density-external quantum efficiency (EQE) graph of PeLED of Example 1 (replacement of 15%), Comparative Example 1 (replacement of 0%), Example 2 (replacement of 10%), Example 3 (replacement of 20%) and Example 4 (replacement of 30%). According to the test results, under the condition of different proportions of ZnBr2 replacing PbBr2, the prepared PeLED showed significant changes in EQE. Specifically, when the proportion of ZnBr2 replacing PbBr2 was 15%, the prepared PeLED showed the highest EQE value, reaching 21.5%, which was far higher than the PeLED without replacement (i.e., replacement of 0%, EQE of 7.1%) and other replacement ratios (such as EQE of 12.7% when replacing 10%, EQE dropped to 8.4% when replacing 20%, and EQE further reduced to 5.0% when replacing 30%). This result fully demonstrates that the replacement of PbBr2 by ZnBr2 at an appropriate proportion can significantly improve the luminous efficiency of PeLED and optimize its photoelectric conversion performance. Substituting 15% of ZnBr2 may effectively adjust the band structure of PeLED, promote the injection and recombination of electrons and holes, and reduce the loss of non-radiative recombination, thereby achieving a significant improvement in EQE. In addition, as the ZnBr2 substitution ratio increases further (such as 20% and 30% substitution), EQE decreases instead. This may be due to the fact that the introduction of excessive ZnBr2 leads to the disorder of the internal structure of PeLED, increases defect states and non-radiative recombination centers, and thus affects the luminous efficiency and photoelectric performance.
[0092] Figure 7The electroluminescence (EL) spectra of the PeLED devices of Example 1 (15% replacement), Comparative Example 1 (0% replacement), Example 2 (10% replacement), Example 3 (20% replacement) and Example 4 (30% replacement) are shown. According to the test results, as the substitution ratio of ZnBr2 to PbBr2 increases, the EL spectrum of the prepared device undergoes subtle but clear changes. Specifically, the EL peak wavelength of the device without substitution (0% replacement) is 510nm, and when the substitution ratio increases to 10%, the EL peak wavelength slightly drops to 508nm. Further increasing the substitution ratio to 15%, the EL peak wavelength continues to drop slightly to 507nm, showing a trend of spectral blue shift. However, when the substitution ratio reaches 20% and 30%, the EL peak wavelength stabilizes at 508nm and no longer continues to decline. This spectral change shows that the introduction of ZnBr2 has a significant effect on the luminescence characteristics of PeLED. The differences between ZnBr2 and PbBr2 in crystal structure, energy band structure and electron transition energy level result in the band gap of the luminescent material to increase with the increase of substitution ratio, which in turn causes the luminescent spectrum to move toward the short-wave direction (i.e., blue shift). However, when the substitution ratio exceeds a certain limit (such as 15% substitution), the blue shift trend of the spectrum may tend to saturation. This may be because the stability of the internal structure of the material begins to dominate, limiting further energy band adjustments. In addition, the fact that the EL peak wavelength no longer changes after the substitution ratio exceeds 15% also shows that although the introduction of ZnBr2 has changed the luminescence characteristics of PeLED to a certain extent, too high a substitution ratio may not always be conducive to obtaining better performance.
[0093] Figure 8 The operating life graph of the PeLED device of Example 1 (replacement 15%) and Comparative Example 1 (replacement 0%). According to the test results, at the initial brightness of 100 cd / m 2 Under the condition of 15% replacement of PbBr2 with ZnBr2, the PeLED device exhibited significantly enhanced operation stability. 50 The lifetime of the unsubstituted PeLED device is 3.72 hours. 50Only 0.86 hours. This significant lifetime extension shows that the appropriate amount of ZnBr2 substitution has a positive effect on improving the durability of PeLED devices. The longer device operating life may be attributed to the following reasons: First, the introduction of ZnBr2 may optimize the crystal structure and energy band arrangement of the material, reduce the non-radiative recombination process, and thus improve the luminescence efficiency and device stability. Secondly, the interaction between ZnBr2 and PbBr2 may improve the thermal and chemical stability of the material, so that the device can still maintain good performance under high temperature or long-term working conditions. In addition, the substitution of ZnBr2 may also affect the charge transport and balance inside the device, promote more efficient carrier injection and recombination processes, and further extend the life of the device.
[0094] Fig. 9 The two-dimensional contour pseudo-color map of the spectral stability of the PeLED devices of Example 1 (15% replacement), Comparative Example 1 (0% replacement), Example 2 (10% replacement) and Example 3 (20% replacement) at different voltages. According to the test results, as the proportion of ZnBr2 replacing PbBr2 increases, these PeLED devices all show excellent spectral stability. Regardless of whether it is under low-voltage or high-voltage working conditions, the device spectrum of each example did not shift significantly, which fully demonstrates that the appropriate amount of ZnBr2 substitution does not adversely affect the spectral characteristics of the PeLED device. On the contrary, the introduction of ZnBr2 may indirectly promote the improvement of spectral stability by improving the band structure of the material, reducing defect states or optimizing the charge transfer path.
[0095] Fig.10 The figure shows the current density-external quantum efficiency (EQE) of PeLED of Example 1 (BPCA additive) and Comparative Example 2 (PABP additive). According to the test results, when ZnBr2 replaces 15% of PbBr2, the PeLED device using BPCA additive shows an impressive external quantum efficiency (EQE) of up to 21.5%, which is almost four times that of the device using PABP additive (EQE is 5.6%). This huge gap directly illustrates the excellent performance of BPCA additive in promoting exciton formation, reducing non-radiative recombination and improving light extraction efficiency.
[0096] The above content describes the embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A composition of zinc-lead halide quasi-two-dimensional green light perovskite, characterized in that: The raw materials for preparing the zinc-lead halide quasi-two-dimensional green light perovskite composition include: tert-butyl [bis(4-methoxyphenyl)phosphinoyl]carbamate and zinc bromide.
2. The composition of zinc-lead halide quasi-two-dimensional green light perovskite according to claim 1, characterized in that: The raw materials for preparing the zinc-lead halide quasi-two-dimensional green light perovskite composition also include: cesium bromide, lead bromide, zinc bromide and phenylbutylamine bromide.
3. The composition of zinc-lead halide quasi-two-dimensional green light perovskite according to claim 2, characterized in that: In terms of molar ratio, the cesium bromide, the lead bromide, the zinc bromide, the phenylbutylammonium bromide and the [bis(4-methoxyphenyl)phosphinoyl]carbamic acid tert-butyl ester are: 1-1.2: 1-x: x: 0.4-0.8: 0.1-0.5; 0<x≤30%。 4. A method for preparing a composition of zinc-lead halide quasi-two-dimensional green light perovskite as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: in a solution state, cesium bromide, lead bromide, zinc bromide, phenylbutylamine bromide and [bis(4-methoxyphenyl)phosphinoyl]carbamic acid tert-butyl ester are mixed and heated to react to obtain the product.
5. The preparation method according to claim 4, characterized in that: In the solution state, Pb 2+ With Zn 2+ The sum of their concentrations is 0.04-0.06 mol / L.
6. A perovskite film, characterized in that: The perovskite film is prepared from the composition of zinc-lead halide quasi-two-dimensional green light perovskite according to any one of claims 1 to 3.
7. A perovskite light-emitting diode, characterized in that: It comprises an anode conductive glass layer, a hole transport layer, an interface modification layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer which are stacked in sequence, and the perovskite light-emitting layer is the perovskite film according to claim 6.
8. The perovskite light-emitting diode according to claim 7, characterized in that: The material of the electron transport layer includes at least one of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene, 2,4,6-tris[3-(diphenylphosphinoyl)phenyl]-1,3,5-triazole, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline and 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine.
9. The perovskite light-emitting diode according to claim 7, characterized in that: The material of the hole transport layer includes poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine).
10. The perovskite light-emitting diode according to claim 7, characterized in that: The material of the interface modification layer includes at least one of lithium fluoride and oxoacid-type lithium salt.
Citation Information
Patent Citations
Green light emitting diode device and preparation method thereof
CN116322101A
Green-light perovskite light-emitting layer, perovskite light-emitting diode and preparation method of green-light perovskite light-emitting layer
CN116406209A